Adverse effects of nanosilver on human health and the environment. (August 2019) - Rezvani, Ehsan; Rafferty, Aran; McGuinness, Cormac; Kennedy, James
Graphical abstract: Abstract: Silver and silver nanoparticles (AgNPs) exhibit antimicrobial properties against some bacteria, fungi and viruses, however, the ever-increasing application of nanosilver in consumer products, water disinfection and healthcare settings, have raised concerns over the public health/environmental safety of this nanomaterial. The current ubiquity of nanosilver may result in repeated exposure through various routes (skin, inhalation, or ingestion) which may lead to health complications. While there are a number of review articles and case studies published to date on the subject, an updated coherent review that clearly delineates thresholds and safe doses is lacking. Thus, it is plausible to have an overview of the most recent findings on the threshold limits, safe doses of silver and its related nanoscale forms, and the needed actions to ensure the safety and health of human, terrestrial and aquatic lives. This review provides an account of the effects of nanosilver in our daily lives. Statement of Significance: This manuscripts is a review of the toxicity of nanosized silver. With respect to the existing literature, it goes beyond stating that there is a knowledge gap, drawing the attention of a wider readership to the ever-growing evidence of nanosilver toxicity to human and nature, and outlining the dose thresholds based on comprehensive data mining and visualisation. There are nearly 500 consumer products that claim to contain nanosilver. Thus, we trust a review of recent conclusive findings is timely. This manuscript is in line with the scope of the Journal, enabling a better understanding of the biological response to a widely-used bionanomaterial. Moreover, it provides a bigger picture of the link between surface properties and biocompatibility of nanosilver in different forms.